TEACHER LIBRARIAN CAPABILITY IN CLASS MANAGEMENT OF THE LEARNING PROCESS IN INTEGRATED MADRASAH IBTIDAIYAH - Wa Mirna; Nana Ronawan Rambe (UIN Sumatera Utara, 2021)
The purpose of this study is to determine the librarian teacher's ability to manage the learning process in the classroom. This type of research is qualitative in the sense that it generates descriptive data in the form of written and oral words based on the behavior of the people observed. The researcher employs a purposive sampling technique to gather the necessary information. and the principal. The results showed that the fifth grade teacher at MI Terpadu Almadinah's classroom management ability in the learning process was quite good, as in the application of classroom management principles such as warmth and enthusiasm, challenge, variety, flexibility, emphasis on positive things, and inculcation of discipline. While designing the learning process and the physical environment of the classroom, it is possible to create a positive learning climate; however, there are still obstacles in terms of using media methods and completeness in the classroom.